Peran Politik Perempuan Anggota DPRD Kabupaten Nias Selatan Periode 2019-2024 dalam Pembahasan Perda No.2 Tahun 2021 - Syamsuddin Agung Putra Harita (Pusat Studi Wanita, Univesitas Kristen Indonesia, 2021)
This article will explain the role and involvement of women which is very important in the world of politics, considering that all policies and decisions related to public issues are determined in the political sphere, especially the legislature. This study uses a qualitative research method with a descriptive approach to analyze and describe the political role of women. The results showed that the members of the PDIP faction in the DPRD Nias Selatan could not represent the aspirations of the community, especially in fighting for the rights of women in the DPRD Kabupaten Nias Selatan. This is influenced by several factors, first, the number of female DPRD members is still low and limited. Second, the community in conveying their aspirations is more on infrastructure development than on gender issues. Third, the lack of support given to women DPRD members by other DPRD members. Fourth, the ability and knowledge of women DPRD members is still limited and not confident